“BÁNH TRÔI NƯỚC” AND THREE ENGLISH VERSIONS OF TRANSLATION: A SYSTEMIC FUNCTIONAL COMPARISON - Van, Hoang Van (VNU Journal of Foreign Studies, 2018)
This paper is concerned with a comparison of the three English versions of translation: “The Floating Cake” translated by John Balaban, “The Cake That Drifts In Water” translated by Huỳnh Sanh Thông and “Floating Sweet Dumpling” translated by Marilyn Chin with the source poem “Bánh trôi nước” by the Vietnamese renowned poetess Hồ Xuân Hương. The theoretical framework employed for analysis and comparison of the texts is systemic functional linguistics. The results show that there are both similarities and differences between the translated versions and the source poem, and between the translated versions in terms of ideational, interpersonal and textual meanings. The results also indicate that there are more differences in lexical choice (the choice of words and groups/phrases) than in syntactic choice (the choice of transitivity, mood, and thematic patterns) between the three translated versions and the original poem, and between the three translated versions.